Macroscopic and microscopic evaluation of flapless alveolar perforations on experimental tooth movement - Jose Luis Munoz Pedraza; Mariana Marquezan; Lincoln Issamu Nojima; Matilde da Cunha Gonçalves Nojima (Dental Press Journal of Orthodontics)
Abstract Objective: The aim of this study was to evaluate a flapless surgical technique as an alternative to traditional alveolar corticotomy used to accelerate orthodontic tooth movement (OTM). Methods: To induce OTM in Wistar rats, 40 cN of orthodontic force were applied to the maxillary left first molars. Forty rats were distributed into control groups (CG1, CG3, CG7 and CG14) and experimental groups (n= 5), in which alveolar perforations were made using a spear-shaped guide bur (EG1, EG3, EG7, EG14). Euthanasia dates were set at 1, 3, 7 and 14 days, respectively, after tooth movement began. The amount of OTM was measured with a caliper, and osteoclasts present in the periodontal ligament of the mesial root of the moved tooth were counted by means of histological evaluation (tartrate-resistant acid phosphatase staining, TRAP). Results: Although there was no difference in the amount of OTM within subgroups of corresponding experimental periods (p> 0.05), when EG14 and CG14 were compared, a larger number of osteoclasts was counted in the experimental group (p< 0.00). Conclusion: The authors concluded that flapless cortical alveolar perforations led to more intense osteoclastic activity on the fourteenth day; nevertheless, no evidence of accelerated OTM could be noted.